Comparison of the effectiveness of self-compassion training and integrated mindfulness-cognitive behavioral therapy on parenting stress and experiential avoidance in mothers with slow-paced children - Roohimotlagh, Sharareh; Eftekhar Saadi , Zahra; Makvandi , Behnam; Hafezi, Fariba (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The present study was conducted with the aim of comparing the effectiveness of self-compassion-based training and integrated mindfulness-cognitive behavioral therapy on parenting stress and experiential avoidance in mothers with slow-paced children. Methods: The current research was an experimental type with a pre-test-post-test design and follow-up with a control group. The statistical population of the current study included all mothers with slow-walking children who lived in Tehran in the winter of 2018 and their children were covered by exceptional educational centers, from which 45 mothers were selected using a targeted sampling method. And randomly, 15 people were placed in two experimental groups and control group. In order to collect data, Abidin's parental stress index questionnaire (1995) and Bund et al.'s acceptance and action questionnaire (2011) were used. Educational sessions based on self-compassion based on the protocol of Gilbert et al. (2014) and integrated mindfulness-cognitive behavioral therapy based on the protocol of Frances, Shavier, Cain, Anticott and Mitos (2020), during eight 90-minute sessions weekly and it was implemented for two months. Analysis of variance with repeated measurements and spss software were used to analyze the data. Results: The results showed that training based on self-compassion and integrated mindfulness-cognitive behavioral therapy on parenting stress (F=90.04, P